Working Memory as an Indicator for Comparative Cognition – Detecting Qualitative and Quantitative Differences - Hahn, Lukas Alexander; Rose, Jonas (Frontiers in Psychology, 2020)
Working memory (WM), the representation of information held accessible for manipulation, is an essential component of higher cognitive abilities. It allows for complex behaviors that go beyond simple stimulus-response associations and inflexible behavioral patterns. WM capacity determines how many different pieces of information can be used for these cognitive processes and in humans it correlates with fluid intelligence. WM might be a useful tool for comparison of cognition across species. It can be tested using simple behavioral protocols, based on operant conditioning, in a multitude of different species. Species-specific contextual variables that influence an animal's performance on a non-cognitive level can be controlled by adapting the WM paradigm. The neuronal mechanisms by which WM emerges in the brain, as sustained neuronal activity, are comparable between species studied, as are the areas of the brain in which WM activity can be measured. Thus WM is comparable between vastly different species, accounting for specific contextual variables and unique adaptations. By approaching the question of 'general cognitive abilities' or 'intelligence' within the animal kingdom from the perspective of WM, the complexity of the core question at hand is reduced to a fundamental memory system required to allow for complex cognitive abilities. This article argues that measuring WM can be a suitable addition to the toolkit of comparative cognition. By measuring WM on a behavioral level and going beyond behavior, to the underlying physiological processes, qualitative and quantitative differences in cognition between different animal species can be identified, free of contextual restraints.